Efficient and Scalable Synthesis of 6,6-Dimethyl-3-oxabicyclo [3.1.0]hexan-2-one through Organocatalyzed Desymmetrization and Chemoselective Reduction - Tintori, Guillaume; Jacob, Clément; Delsarte, Christine; Potié, François; Grimaud, Laurence; Vitale, Maxime; Echeverria, Pierre-Georges (Synthesis, 2024)
The development of a robust process to 6,6-dimethyl-3-oxabicyclo[3.1.0]hexan-2-one, a key intermediate toward several active compounds of interest, is described. A scalable organocatalyzed desymmetrization was first studied and the reaction proved to be compatible with standard dilution. A kinetic study was performed to elucidate substrate and catalyst concentration dependences. Next, a chemoselective reduction of the carboxylic acid was developed. The scalability was demonstrated on 100 g scale through a fully telescoped process.
Keywords: desymmetrization; organocatalysis; chemoselective carboxylic acid reduction; process development; kinetics; scale-up